A bacterial genotoxin causes virus reactivation and genomic instability in Epstein–Barr virus infected epithelial cells pointing to a role of co‐infection in viral oncogenesis. Issue 1 (29th October 2018) - Frisan, Teresa; Nagy, Noemi; Chioureas, Dimitrios; Terol, Marie; Grasso, Francesca; Masucci, Maria G.
Abstract : We have addressed the role of bacterial co‐infection in viral oncogenesis using as model Epstein–Barr virus (EBV), a human herpesvirus that causes lymphoid malignancies and epithelial cancers. Infection of EBV carrying epithelial cells with the common oral pathogenic Gram‐negative bacterium Aggregatibacter actinomycetemcomitans ( Aa ) triggered reactivation of the productive virus cycle. Using isogenic Aa strains that differ in the production of the cytolethal distending toxin (CDT) and purified catalytically active or inactive toxin, we found that the CDT acts via induction of DNA double strand breaks and activation of the Ataxia Telangectasia Mutated (ATM) kinase. Exposure of EBV‐negative epithelial cells to the virus in the presence of sub‐lethal doses of CDT was accompanied by the accumulation of latently infected cells exhibiting multiple signs of genomic instability. These findings illustrate a scenario where co‐infection with certain bacterial species may favor the establishment of a microenvironment conducive to the EBV‐induced malignant transformation of epithelial cells. Abstract : What's new? Little is known about the influence of coinfections, especially of bacteria, on viral oncogenesis. Here, the authors examined the effect of the cytolethal distending toxin (CDT) of Aggregatibacter actinomycetemcomitans, a common oral pathogen, on epithelial cells infected with Epstein–Barr virus (EBV). Exposure of EBV+ cells to CDT induced viral reactivation, while exposure of EBV‐ cells to low amounts of CDT led to the accumulation of latently infected cells upon infection, pointing to a multi‐layered role of bacterial co‐infection in viral oncogenesis.